Comparison of Topical Treatment Preferences of Physicians in Dermatological Diseases - Aksoy, Hasan; Aslan Kayıran, Melek; Özger, Hümeyra (European Journal of Therapeutics, 2023)
Objective: Regardless of their specialty, physicians frequently encounter dermatological conditions. We aimed to determine the topical medication choices of physicians for various dermatoses and to identify differences in preferences between dermatologists and non-dermatologist physicians. Methods: Using an online survey, physicians were asked to select three preferred topical antibiotics/antiseptics, antifungals, and corticosteroids when treating a pyoderma, dermatophytosis, or a dermatosis necessitating topical corticosteroid therapy. Statistical analysis was performed using Statistical Package for the Social Sciences v.27. Results: Among 358 physicians, 24.0% were dermatologists, and 76.0% were non-dermatologist physicians. The mean age was 38.40, and the average duration of medical practice was 14.04 years. The most frequently chosen topical antibacterials were fusidic acid (74.3%) and mupirocin (65.9%); topical antifungals were isoconazole nitrate + diflucortolone valerate (56.4%), tioconazole (27.7%), and naftifine (25.1%); and topical corticosteroids were clobetasol propionate (38.5%), methylprednisolone aceponate (36.6%), and mometasone furoate (34.6%). Dermatologists used nitrofurazone and izokonazol nitrate + diflucortolone valerate less frequently compared to non-dermatologists (0% vs. 27.6% and 8.1% vs. 71.7%, respectively; p-values <0.001). Family physicians/general practitioners constituted the largest group selecting clobetasol propionate (28.3%). Conclusion: Physicians in our country predominantly choose fusidic acid and mupirocin as topical antibiotics, aligning with existing literature. However, nitrofurazone, causing contact dermatitis, and corticosteroid-containing antifungals with the potential for complications due to inappropriate use are frequently preferred by non-dermatologist physicians but not by dermatologists. The bold choice of clobetasol propionate, an ultrapotent topical corticosteroid, by family physicians/general practitioners is an important issue to address during medical education and post-graduation.